1983
DOI: 10.1017/s0094837300007703
|View full text |Cite
|
Sign up to set email alerts
|

Small mammal bone accumulations produced by mammalian carnivores

Abstract: Small mammal bone assemblages from the scats of three families of mammalian carnivores are described here as a means of assessing paleontological bone assemblages. These are the Viverridae, Canidae, and Mustelidae. Marking behavior by the carnivores or their use of latrine areas can produce concentrations of bone comparable with those produced from owl pellets, but the nature of the bone assemblages is very different. Skeletal element preservation has a characteristic pattern related to the relative strength o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
120
3
20

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(149 citation statements)
references
References 39 publications
4
120
3
20
Order By: Relevance
“…These works describe interspecific bone patterns of contemporary agents of bone deposition, assuming that each deposition agent produces a fixed bone pattern, with little or no intraspecific variation. Taphonomic studies have concentrated on definitive descriptions of bone patterns produced by several modern predators (Dodson & Wexlar, 1979;Korth, 1979;Hoffman, 1988;Andrews, 1990a;Kusmer, 1990), often characterizing composition and fragmentation of bone and teeth remains left by diverse predators (Noe-Nygaard, 1977;Behrensmeyer & Dechant Boaz, 1980;Gifford, 1981;Andrews & Evans, 1983;Andrews, 1990a, b).…”
mentioning
confidence: 99%
“…These works describe interspecific bone patterns of contemporary agents of bone deposition, assuming that each deposition agent produces a fixed bone pattern, with little or no intraspecific variation. Taphonomic studies have concentrated on definitive descriptions of bone patterns produced by several modern predators (Dodson & Wexlar, 1979;Korth, 1979;Hoffman, 1988;Andrews, 1990a;Kusmer, 1990), often characterizing composition and fragmentation of bone and teeth remains left by diverse predators (Noe-Nygaard, 1977;Behrensmeyer & Dechant Boaz, 1980;Gifford, 1981;Andrews & Evans, 1983;Andrews, 1990a, b).…”
mentioning
confidence: 99%
“…Digestion in the otter produces feces in which the bones tend to be broken and digested like in most other mammalian carnivores. For example, Andrews and Evans (1983), Andrews (1990) and Matthews (2002) have shown that feces of small felids generally contain extremely broken bones with high levels of rounding and polishing produced by digestion. They also found that scats of small canids contain digested bones, but the degree of breakage is slightly less than in small felids.…”
Section: Discussionmentioning
confidence: 99%
“…There are many descriptions of current assemblages originating from various predators such as nocturnal and diurnal birds of prey (Mayhew 1977;Dodson & Wexlar 1979;Andrews 1990;Laroulandie 2002), crocodiles (Fisher 1981) and carnivores (Andrews & Evans 1983;Andrews 1990;Mondini 2001;Campmas & Beauval 2008). Modern carnivores produce feces containing bones that display varying degrees of damage and digestion.…”
Section: Introductionmentioning
confidence: 99%
“…Além disso, o grande número de falanges e metapodiais completos na tafocenose estudada, os quais, segundo Behrensmeyer & Dechant-Boaz (1980) são as partes do esqueleto preferidas pelos predadores, pode sugerir que os animais encontrados na fenda estudada não faziam parte da dieta dos predadores locais. Andrews & Evans (1983) e Faith et al (2007 ao analisarem, respectivamente, assembleias geradas por mamíferos carnívoros e mudanças na representatividade óssea produzidas por carniceiros (hienas), observaram que os elementos proporcionalmente mais encontrados em concentrações ósseas de vertebrados sob interferência de carnívoros e carniceiros são úmeros e tíbias, os quais não são abundantes na tafocenose da "Fenda 1968". Outro fator que deve ser levado em consideração é que a quantidade de animais carnívoros paleocênicos representada na bacia de São José de Itaboraí aparentemente é baixa se comparada à quantidade de herbívoros/frugívoros registrada (ver em Bergqvist et al, 2006 a listagem das famílias presentes na bacia).…”
Section: Discussionunclassified